Pengembangan Model Manajemen Transformatif Pondok Pesantren - Faruk, Roizatul; Mustajib (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2023)
The purpose of this research and development is to find a transformative management model that runs at the Ali Maksum Foundation, Pondok Pesantren Krapyak Yogyakarta. The research method used is qualitative analysis with an evaluative approach. The subjects of the study were determined by purposive sampling. The data collection method uses in-depth interviews, participant observations, and documentation, while the validity of the data uses source trianggulation techniques. Data analysis techniques use qualitative data presentation techniques with a discretionary evaluation analysis model. The results of the research of the Ali Maksum Foundation of Krapyak Islamic Boarding School have not implemented transformative management optimally